1987
DOI: 10.1159/000215760
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Coronary Artery Disease and Basal Fibrinolysis

Abstract: Basal venous blood levels of several components of the fibrinolytic enzyme system (plasminogen activator, plasminogen, fibrin degradation products, α2-antiplasmin, and α2-macroglobulin) were measured in 100 white men with angiographically defined coronary artery disease. The tests of fibrinolysis were not related to the severity of coronary artery disease, as indicated either by the number of vessels involved or by a coronary score system. Fibrinogen levels, however, did show a modest ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…This hemostatic factor may well be active in the atherosclerotic process, as sever al studies have shown a significant correlation between plasma fibrinogen and the degree of coronary atherosclerosis, defined as the num ber of coronary vessels with hemodynamically relevant stenoses [27][28][29], The present study showed that high-risk patients with in termittent claudication had higher plasma levels of fibrinogen than both the high-risk patients without intermittent claudication and the low-risk subjects. In addition, highrisk patients without intermittent claudica tion had higher fibrinogen levels compared to low-risk subjects.…”
Section: Fibrinogensupporting
confidence: 61%
“…This hemostatic factor may well be active in the atherosclerotic process, as sever al studies have shown a significant correlation between plasma fibrinogen and the degree of coronary atherosclerosis, defined as the num ber of coronary vessels with hemodynamically relevant stenoses [27][28][29], The present study showed that high-risk patients with in termittent claudication had higher plasma levels of fibrinogen than both the high-risk patients without intermittent claudication and the low-risk subjects. In addition, highrisk patients without intermittent claudica tion had higher fibrinogen levels compared to low-risk subjects.…”
Section: Fibrinogensupporting
confidence: 61%
“…Our study, conducted on two groups of asymptomatic, moderately dyslipidemic patients (phenotypes lib and IIa) with no other cardiovascular risk factors, shows that moderate hypertriglyceridemia determines an increased PAI-1 activity in baseline conditions with no prejudice for the fibrinolytic system, and that moderate hypercholesterolemia is associated with higher Lp(a) concentrations, No alterations were observed in the platelet activation indexes. The im- portance of these results lies in the fact that PAl-1 is considered to be an additional risk factor for the atherosclerotic and thrombotic process [12,14,34] by inhibiting the fibrinolytic mechanism and reducing the removal of fibrin deposits [35]. Many studies have shown the presence of high plasma concentrations of PAI-1 in CHD patients [20][21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies on asymptomatic patients with heavy dyslipidemia [9][10][11][12][13] and also on patients with coronary disease (CHD) [14][15][16][17][18][19] have confirmed the close link between hypertriglyceridemia, increased platelet activity, and reduced fibrinolysis. A positive correlation has also been discovered between the plasminogen tissue activator inhibitor (PAI-1) and high triglyceride concentrations in the blood [14][15][16][17][18][19]. More recently, the Prospective Cardiovascular Munster Study [20] and the Framingham Study [21] have shown that hypertriglyceridemia is an additional risk factor for CHD, especially when high triglyceride levels are associated with low, high-density lipoprotein (HDL-C) values or with a high ratio between total cholesterol and HDL-C.…”
Section: Introductionmentioning
confidence: 99%
“…From these considerations, it can be deduced that in PVD, higher blood concentrations of TGs, even if within normal limits, are accompanied by lowerAPI values and, therefore, indicate a worse prognosis of the stage II PVD. A relationship between TG values and the fibrinolytic system should also be taken into account in interpreting the results (79)(80)(81)(82)(83)(84)(85). HDL-C, and Apos Al and B are the variables that make it easier to distinguish PVD patients from the ~c~n~rc~Is,'ar~d these parameters constitute important risk factors not only for ischemic coronaropathy.…”
Section: No Significant Difference Between Pvd Patientsmentioning
confidence: 99%